Potential of herbs in skin protection from ultraviolet radiation - Korać, Radava R.; Khambholja, Kapil M. (Pharmacognosy Reviews, 2011)
Herbs have been used in medicines and cosmetics from centuries. Their potential to treat different skin diseases, to adorn and improve the skin appearance is well-known. As ultraviolet (UV) radiation can cause sunburns, wrinkles, lower immunity against infections, premature aging, and cancer, there is permanent need for protection from UV radiation and prevention from their side effects. Herbs and herbal preparations have a high potential due to their antioxidant activity, primarily. Antioxidants such as vitamins (vitamin C, vitamin E), flavonoids, and phenolic acids play the main role in fighting against free radical species that are the main cause of numerous negative skin changes. Although isolated plant compounds have a high potential in protection of the skin, whole herbs extracts showed better potential due to their complex composition. Many studies showed that green and black tea (polyphenols) ameliorate adverse skin reactions following UV exposure. The gel from aloe is believed to stimulate skin and assist in new cell growth. Spectrophotometer testing indicates that as a concentrated extract of Krameria triandra it absorbs 25 to 30% of the amount of UV radiation typically absorbed by octyl methoxycinnamate. Sesame oil resists 30% of UV rays, while coconut, peanut, olive, and cottonseed oils block out about 20%. A “sclerojuglonic” compound which is forming from naphthoquinone and keratin is the reaction product that provides UV protection. Traditional use of plant in medication or beautification is the basis for researches and making new trends in cosmetics. This review covers all essential aspects of potential of herbs as radioprotective agents and its future prospects.
Keywords: Antioxidants; cosmetics; plant extract; sunblocks; Ultra violet radiation